Kebersihan Tangan dan Infeksi Cacing Enterobius Vermicularis pada Anak Sekolah Dasar - Ahmad Heru Sopyan; Yuke Andriane; Ismet Muchtar Nur (Bandung Conference Series: Medical Science, 2023)
Abstract. Enterobiasis is an infection with the worm Enterobius vermicularis which is still a global public health problem in both developed and developing countries. One of the factors that increases the risk of Enterobiasis is poor hand hygiene. The purpose of this study was to find out whether there is a relationship between hand hygiene and Enterobiasis in grade 6 students at SDN Jayamakmur 1 Karawang, West Java, in 2022. The type of research was analytic observational with a cross sectional research design. The research population was 6th grade students at SDN Jayamakmur 1 Karawang, West Java, with a total sample of 32 people. Data collection was carried out using a hand hygiene questionnaire and anal swab examination and analyzed using the Chi-square test. The results of the study showed that the number of students who had good hand hygiene and those who had poor hand hygiene were almost the same and the frequency distribution of Enterobiasis examinations showed that most of the respondents did not experience Enterobiasis. The results showed that there was a relationship between hand hygiene and Enterobiasis in grade 6 students at SDN Jayamakmur 1 Karawang, West Java, in 2022 (P-value = 0.006). Hand hygiene is important in everyday life because hands are the first medium that is very often contaminated with parasites, especially Enterobius vermicularis, which can cause Enterobiasis. Abstrak. Enterobiasis merupakan infeksi cacing Enterobius vermicularis yang masih menjadi masalah kesehatan masyarakat global baik di negara maju maupun berkembang. Salah satu faktor yang meningkatkan risiko Enterobiasis adalah kebersihan tangan yang kurang baik. Tujuan penelitian ini untuk mengetahui apakah terdapat hubungan kebersihan tangan dengan Enterobiasis pada siswa kelas 6 SDN jayamakmur 1 Karawang Jawa Barat tahun 2022. Jenis penelitian adalah analitik observasional dengan desain penelitian cross sectional. Populasi penelitian adalah siswa kelas 6 di SDN Jayamakmur 1 Karawang Jawa Barat dengan jumlah sampel sebanyak 32 orang. Pengumpulan data dilakukan dengan kuesioner kebersihan tangan dan pemeriksaan anal swab serta dianalisis dengan uji Chi-square. Hasil penerlitian menunjukan jumlah siswa yang memiliki kebersihan tangan yang baik dengan yang memiliki kebersihan tangan yang buruk hampir sama banyak dan distribusi frekuensi pemeriksaan Enterobiasis sebagian besar responden tidak mengalami Enterobiasis. Hasil penelitian menunjukan terdapat hubungan antara kebersihan tangan dengan Enterobiasis pada siswa kelas 6 SDN Jayamakmur 1 Karawang Jawa Barat tahun 2022 (P-value = 0,006). Kebersihan tangan merupakan hal penting dalam kehidupan sehari-hari karena tangan merupakan perantara pertama yang sangat sering terkontaminasi parasit khususnya Enterobius vermicularis sehingga dapat menyebabkan Enterobiasis.